DETERMINAN KINERJA USAHA MIKRO KECIL MENENGAH (UMKM) ALAT TEKNIK DI PASAR HWI LINDETEVES JAKARTA - Cahya, Kenny Oktavianus; Christian, Michael (Jurnal Pengabdian dan Kewirausahaan, 2020)
The ebb and flow of passion for Micro, Small and Medium Enterprises in Indonesia, especially in Jakarta, signals that people's tastes have changed apart from the purchasing power factor. As an area for buying and selling technical equipment that tends to be homogeneous, the HWI Lindeteves Jakarta market has an interesting phenomenon to research. This study aims to explain the effect of Market Orientation and Entrepreneurship Orientation on Business Performance. This quantitative research uses multiple regression analysis for data analysis. The measuring instrument used is SPSS 23.0. The results of this study explain that business performance is affected by market orientation. Furthermore, Business Performance is also influenced by Entrepreneurial Orientation. Simultaneously, this study explains that business performance is influenced by market orientation and entrepreneurial orientation. The better the company strategy is related to understanding Market Orientation and Entrepreneurship Orientation, the better it will support Business Performance. On the other hand, a low level of market orientation and entrepreneurial orientation can have a low impact on business performance.